2011
DOI: 10.1258/ar.2011.100444
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal tuberculosis – imaging using low-end and advanced modalities for developing and developed countries

Abstract: Musculoskeletal involvement by TB is rare in comparison to other forms of the disease. It most commonly involves the spine but can also involve large weight-bearing joints, long bones, the skull and the soft tissues. Characteristic appearances of musculoskeletal TB are described for numerous imaging modalities in this paper but it is also highlighted that when based on imaging appearances alone, there is always a differential diagnosis, including other infections and malignancies. Awareness of of TB as a possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The main route of spread is haematogenous, from lungs, or via activation of dormant infection in bone or joint post-trauma. 27 Cases of musculoskeletal TB are usually subclassified as tubercular spondylitis (50%) (popularly called Potts' spine), peripheral tuberculous arthritis (60%), osteomyelitis (38%), and soft tissue TB, including tenosynovitis and bursitis. [28][29][30] [ ( F i g u r e _ 2 ) T D $ F I G ] [ ( F i g u r e _ 3 ) T D $ F I G ]…”
Section: Musculoskeletal Tuberculosismentioning
confidence: 99%
“…The main route of spread is haematogenous, from lungs, or via activation of dormant infection in bone or joint post-trauma. 27 Cases of musculoskeletal TB are usually subclassified as tubercular spondylitis (50%) (popularly called Potts' spine), peripheral tuberculous arthritis (60%), osteomyelitis (38%), and soft tissue TB, including tenosynovitis and bursitis. [28][29][30] [ ( F i g u r e _ 2 ) T D $ F I G ] [ ( F i g u r e _ 3 ) T D $ F I G ]…”
Section: Musculoskeletal Tuberculosismentioning
confidence: 99%
“…While CT may also demonstrate para‐spinal soft‐tissue masses, its strength is in identifying bony involvement 3 . In our patient, the primary site of bone involvement was the spine, whereas the multiple rib changes of scalloping and sclerosis were more indicative of pressure changes from the intrathoracic extrapulmonary abscesses.…”
Section: Discussionmentioning
confidence: 72%
“…19 Other complications and associations that can also be seen on CT, that are not related to the airway occlusion and include pericardial effusions, axillary adenopathy, 22 and musculoskeletal involvement. 23 Goussard et al 13 described the clinical, radiological, and bronchoscopy findings of expansile pneumonia in 24 children with TB. They showed that in patients with obstruction of more than 75% on fibreoptic bronchoscopy (FB) there was liquefaction on CT, while there was no liquefaction was present in obstructions less than 75%.…”
Section: Discussionmentioning
confidence: 99%